The efficacy of immediate lymphatic reconstruction in preventing breast cancer-related lymphedema: long-term follow-up study - Ki-Jae Kim; Sun-Hyeok Kim; Seung-Pil Jung; Eul-Sik Yoon; Jae-Ho Chung (Journal of Plastic Surgery and Hand Surgery)
Background: Immediate lymphatic reconstruction (ILR) has emerged as an effective intervention to reduce breast cancer-related lymphedema, which affects 2–30% of patients who undergo axillary lymph node dissection (ALND). Our previous research validated ILR’s effectiveness over 14 months, but the duration was short and warranted further study. This study provides long-term evidence of its benefits in a well-defined patient cohort.